Islamic Moral Ethics: The Foundations for Good Governance, Management, and Civilizational Advancement - Afifi, Abdullah A (Perwakilan: Journal of Good Governance, Diplomacy, Customary Institutionalization and Social Networks, 2024)
Islamic moral ethics, in essence, are not something new in Islamic knowledge. Many classical books mention the components that give advancement in governance, like Madinat al-Fadhilah by al-Farabi, Siyar al-Muluk by Nizam al-Mulk, Muqaddimah by Ibn Khaldun, al-Ahkam al-Sulthaniyah by al-Mawardi, Siraj al-Muluk by al-Turtushi, as-Siyasah al-Shariyyah by Ibn Taymiyah, Nasihat al-Mulk by al-Ghazali and many more. This article explores Islamic moral ethics as foundational pillars and their roles in shaping effective governance, ethical management, and the advancement of civilization. Islamic moral ethics need to be highlighted to answer the needs of today's modern governance and to be more just, compassionate, and wise for the benefit of the people. Drawing from core Islamic values such as justice ('adl), trust (amanah), compassion (rahmah), social welfare (maslahah), and collective wisdom (hikmah), the study demonstrates how these principles not only guide individual conduct but also inform institutional structures and advancement. Integrating Islamic moral ethics into governance ensures transparency, accountability, and public welfare. At the same time, it promotes fairness, responsibility, and inclusive decision-making in management. The article further compares Islamic values with modern governance and management, revealing strong areas of convergence and unique contributions. The study affirms that embedding Islamic moral ethics into contemporary governance and management frameworks can foster sustainable development, institutional trust, and long-term civilizational progress in an increasingly complex global environment.